Quantification of Myocardial Mass Subtended by a Coronary Stenosis Using Intracoronary Physiology. (August 2019) - Murai, Tadashi; van de Hoef, Tim P.; van den Boogert, Thomas P.W.; Wijntjens, Gilbert W.M.; Stegehuis, Valérie E.; Echavarria-Pinto, Mauro; Hoshino, Masahiro; Yonetsu, Taishi; Planken, R. Nils; Henriques, José P.S.; Escaned, Javier; Kakuta, Tsunekazu; et al.
Abstract : Background: In patients with stable coronary artery disease, the amount of myocardium subtended by coronary stenoses constitutes a major determinant of prognosis, as well as of the benefit of coronary revascularization. We devised a novel method to estimate partial myocardial mass (PMM; ie, the amount of myocardium subtended by a stenosis) during physiological stenosis interrogation. Subsequently, we validated the index against equivalent PMM values derived from applying the Voronoi algorithm on coronary computed tomography angiography. Methods: Based on the myocardial metabolic demand and blood supply, PMM was calculated as follows: PMM (g)=APV×D 2 ×π/(1.24×10 − 3 ×HR×sBP+1.6), where APV indicates average peak blood flow velocity; D, vessel diameter; HR, heart rate; and sBP, systolic blood pressure. We calculated PMM to 43 coronary vessels (32 patients) interrogated with pressure and Doppler guidewires, and compared it with computed tomography–based PMM. Results: Median PMM was 15.8 g (Q1, Q3: 11.7, 28.4 g) for physiology-based PMM, and 17.0 g (Q1, Q3: 12.5, 25.9 g) for computed tomography–based PMM ( P =0.84). Spearman rank correlation coefficient was 0.916 ( P <0.001), and Passing-Bablok analysis revealed absence of both constant and proportional differences (coefficient A: −0.9; 95% CI, −4.5 to 0.9; and coefficient B, 1.00; 95% CI, 0.91 to 1.25]. Bland-Altman analysis documented a mean bias of 0.5 g (limit of agreement: −9.1 to 10.2 g). Conclusions: Physiology-based calculation of PMM in the catheterization laboratory is feasible and can be accurately performed as part of functional stenosis assessment. Abstract : Supplemental Digital Content is available in the text.